A description of some recent research into second languange acquisition and its implications for second language teaching in the Malaysian context / Jelani Sulaiman - Sulaiman, Jelani (Universiti Teknologi MARA Cawangan Pahang, 1989)
This study seeks to describe some recent research into second language acquisition which might help teachers develop a better approach towards more effective second language teaching. In recent years, there have been attempts by teachers of foreign language to analyse some of the general findings of psycholinguistic research with the hope of drawing analogies between first and second language acquisition, and even to the extent of justifying certain teaching methods and techniques on the basis of first language learning principles. They have begun questioning the theories of language learning that had given support to the particular methods which they were practicing in the classrooms. Practically, all teachers have a theory of learning and they are the ones who decide what students will learn and how they will learn it. A teacher plans his or her scheme of work in the belief that a careful selection and arrangement of the teaching material will facilitate learning. Nevertheless, in most cases, a teacher's views about language learning may not be explicit but which exist as a set of covert beliefs. As a result, such teachers may not only be uncritical but also resistant to change. More often than not, they might vary and modify their teaching methods in an unprincipled manner and adhere blindly to the most recent trend in language teaching. It is my fervent hope that this study, besides providing a brief description of the ideas which have surfaced from some recent research into second language acquisition, may well aid language teachers in modifying their approach towards effective second language teaching. This study is organised into three chapters. Chapter I deals with the theory of language 3cquisition, giving insights into first language acquisition, second language learning, and contrastive and error analyses. Chapter II is devoted to the survey of relevant second language theories, focussing on psychological aspects of language learning. Chapter III discusses pedagogical implications of the main ideas postulated by the various theories.